No mercy here: gender, punishment, and the making of Jim Crow modernity - Haley, Sarah (Justice, power, and politics, 2016)
"In the late nineteenth and early twentieth centuries imprisoned black women faced wrenching forms of gendered racial terror and heinous structures of economic exploitation. Exposed to violence and rape, subjugated on chain gangs and as convict laborers, and forced to serve additional time as domestic workers before they were allowed their freedom, black women faced a pitiless system of violence, terror, and debasement. Drawing upon black feminist criticism and a diverse array of archival materials, Sarah Haley uncovers imprisoned women's brutalization in local, county, and state convict labor systems, while also illuminating the prisoners' acts of resistance and sabotage, challenging ideologies of racial capitalism and patriarchy and offering alternative conceptions of social and political life"--